Fast responding hydrogen gas sensors using platinum nanoparticle modified microchannels and ionic liquids - Hussain, Ghulam; Ge, M.; Zhao, C.; Silvester-Dean, Debbie (ELSEVIER SCIENCE BV, 2019)
© 2019 Elsevier B.V.